2016
DOI: 10.12944/cwe.11.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Apple Production in India: A Review

Abstract: Significant variation in mean state of the climate or in its variability persisting for an extended period (typically decades or longer) is referred as climate change. It may be due to natural internal processes or external forcing or persistent anthropogenic changes in the composition of the atmosphere.1 Greenhouse gases like CO2, CH4, N2O, water vapours and ozone re-emit some of solar radiations in the form of short wave radiations to the earth surface and responsible for its warming.2 If they did not perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Water stress is one of the most adverse factors of plant growth and productivity and considered a severe threat for sustainable crop production in the conditions of changing the climate (Singh et al, 2016). Out of total land under stresses in the world, 26% is affected by drought (Alizadeh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Water stress is one of the most adverse factors of plant growth and productivity and considered a severe threat for sustainable crop production in the conditions of changing the climate (Singh et al, 2016). Out of total land under stresses in the world, 26% is affected by drought (Alizadeh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Pentingnya evaluasi kesesuaian agroklimat dapat dilihat dari pengaruh iklim terhadap tanaman. Kondisi iklim seperti suhu tinggi atau rendah dan kelembapan tinggi dapat mempengaruhi kualitas dan kuantitas hasil pertanian (Indriyani et al, 2002;Singh et al, 2016;Rahmanto et al, 2018;Dalhaus et al, 2020). Kondisi iklim juga berhubungan dengan pertumbuhan penyakit perusak tanaman (Supriadi et al, 2015).…”
Section: Pendahuluanunclassified
“…The goal of this paper is to study the key factors, especially the climate processes, responsible for shifting of apple orchards to the high altitudinal region of Himachal Pradesh by analysing the changes in important climate variables. Though previous studies have suggested the climate change to be a factor in the altitudinal shifting of apple orchards [11][12][13][14][15][16][17][18] the exact climate processes responsible for the decrease in cultivated areas and apple production in lower altitudes of Himachal Pradesh are not explored. In this study, we investigated different climatic parameters i.e.…”
Section: Introductionmentioning
confidence: 99%